A Study of Al-Manṭūq wa Al-Mafhūm in QS. An-Nisā’ [4]:3 on Polygamy: An Analysis Based on the Principles of Tafsīr - Muhammad Diaz Supandi; Mahmud Rifaannudin (Tilawah: Journal of Al-Qur'an Studies, 2025)
This abstract presents a comprehensive analysis of QS. An-Nisā’ [4]:3 regarding polygamy through the framework of al-manṭūq and al-mafhūm, aiming to understand both the explicit and implicit meanings of the verse and to synthesize them into a holistic understanding that is socially and ethically relevant. The study employs a qualitative approach using library research, examining classical and contemporary tafsīr, uṣūl al-fiqh literature, and scholarly articles on polygamy and justice, through thematic analysis that situates the verse within its socio-historical context and the objectives of sharī‘ah (maqāṣid al-sharī‘ah). The findings indicate that al-manṭūq provides limited permission for polygamy of up to four wives under the condition of justice, while al-mafhūm emphasizes material, emotional, and social dimensions of justice, making monogamy often the more appropriate choice, with polygamy serving as a conditional allowance in specific social circumstances, such as protection of orphans and widows. The application of the principle of al-manṭūq wa al-mafhūm demonstrates that Islamic law integrates legal certainty with ethical responsibility, emphasizing justice, welfare, and harm prevention. This study contributes to tafsīr scholarship by highlighting the importance of a holistic analysis of the verse, reducing narrow interpretations and misuse, and providing a balanced, ethical, and contextually relevant perspective on Islamic law for modern society.